IMPACT OF DIFFERENT YOGA OCULAR EXERCISES ON EYE HEALTH AMONG INDOOR WORKERS (Journal of Medical & Health Sciences Review, 2025)
OBJECTIVE: To assess impact of different yoga ocular exercises on eye health among indoor workers METHODOLOGY: This study was conducted online. The study comprised forty adults who were symptomatic according to a validated questionnaire. They were divided into two groups based on the eye fatigue symptoms score, with twenty participants in each. The exercise group did yoga ocular exercises on alternate days for up to two months, afterwards the eye fatigue symptoms were assessed again in both groups.RESULTS: Out of 20 subjects in control group, 13(65.0%) had headache sometimes, followed by 5(25.0%) had headache normally, 1(5.0%) more often, and 1(5.0%) had no headache and the time for the headache in study subjects 11(55%) was anytime in the day. About 9(45%) students had headache sometimes while doing near work followed by 4(20%) normally had headache, 4(20%) had more often and 3(15%) had no headache while doing near work.  Out of 20 subjects, 6(30.0%) students had eye fatigue normally and mostly 8(40%) had moderate level of eye fatigue followed by 2(10%) had mild level of eye fatigue, and 4(20%) with severe level of fatigue. Most of the study subjects 8(40%) had complain of eye burn sometimes, followed by 5(25.0%) choose yes, 5(25.0%) more often and 2(10%) had no burning sensation in eyes. The study revealed a notable disparity in headache occurrence during near work was observed, indicating a significant variation between the two groups (p < 0.05). Furthermore, the analysis indicated a significant relationship between eye fatigue severity among both groups (p < 0.05).  Overall, the research findings indicated a significant association between the variables under investigation.CONCLUSION: This study concluded that engaging in yoga ocular exercises, appears to have a positive impact on ocular health. The exercise group demonstrated lower frequencies of headaches, reduced eye fatigue, and improved overall eye-related practices compared to the control group.